DESIGN OF ALUMINUM-BASED SUPERSTRUCTURE FOR TRANSPORT VEHICLES SUBJECTED TO SIDE-IMPACT LOADING - PANUNTUN EKA WIRANTO NIM: 13614042, BAGUS
In these recent years, there has been a significant increase of motor vehicles on the road. However, the growth of accident that occurs on the road also increasing. Side-impact crash is one of the most fatal car accident and one of the cause of the rollover (after event). To reduce the risk of fatality and serious injury, a deep and specific analysis of the structural strength on side-impact loading and the probability of the rollover is a paramount necessity. Static stability factor governs the analysis of the risk of rollover. Static stability factor value is the function of the height of the vehicle’s centre of mass. The height of the vehicle’s centre of mass is determined from empirical method that determines the centre of mass of each component and then establishes the standard of putting the location of the centre of the mass of each component. Thus, the static stability factor is determined from the accumulation of each component's centre of mass. Analysis of the strength of the structure upon side-impact loading is done by using numerical simulation that refers to the side impact regulation FMVSS 214 and further appended using residual space that is regulated in UNECE R66. The simulation of the bus' superstructure are conducted using two different material, STKM 13B steel and Al 6061 T6. Aluminum has lower strength compared to steel. Further strengthening required by using web in the horizontal frame and local thickening on the dominant part that received the load. From the analysis of the rollover probability, it can be concluded that empirical method to determine the car's centre of mass produces a significant accuracy. The analysis of the bus' superstructure upon side-impact loading shows that Al 6061 T6-based structure without reinforcement performs better than the STKM 13B-based structure and also reducing the overall weight to 31%. The reinforcement of the superstructure of the bus using Al 6061 T6 as the base material could increase the toughness against side-impact loading and could reduce the intrusion into the the bus as many as 174 mm compared to the superstructure without reinforcement with steel as the base material.